Habitus as a value lens to link customer engagement and value cocreation. Issue 1 (20th March 2020) - Ellway, Benjamin Piers William; Dean, Alison
Abstract : Purpose: This paper uses practice theory to strengthen the theoretical relationship between customer engagement (CE) and value cocreation (VCC), thereby demonstrating how customers may become engaged and remain engaged through VCC practices. Design/methodology/approach: The study adopts a problematization approach to identify shared assumptions evident in service-dominant logic (SDL) and CE research. Practice theory, as a higher-order perspective, is used to integrate the iterative and cyclical processes of VCC and CE, specifically through the theoretical mechanism of habitus. Findings: Habitus acts as a customer value lens and provides a bridging concept to demonstrate how VCC and CE are joined via sensemaking processes. These processes determine how customers perceive, assess, and evaluate value, how they become engaged through VCC, and how their experience of engagement may lead to further VCC practice. The temporally bound experiences, states, and episodes are accumulated and aggregated through an enduring customer value lens comprised of habituated dispositions, interests, and attitudes. Research limitations/implications: This work responds to calls for research to strengthen the theoretical link between VCC and CE and to take account of customers' lived realities and their contextualized experiences. A key suggestion for future research is the use of a rope metaphor to stimulate thinking about the complex, temporally unfolding, and interrelated processes of VCC and CE. Practical implications: The customer value lens and CE rope are introduced to simplify the complex, abstract, theoretical research on VCC and CE for a nonacademic audience. To understand how customers' value lenses are formed and change, and how a CE rope is strengthened, firms, service designers, and practitioners need to understand sensemaking processes through customer narratives and to use platforms and feedback to support and trigger sensemaking. Originality/value: This paper provides a theoretical mechanism to explain the iterative and cyclical nature of VCC and CE processes and how accumulation and aggregation occur in these processes. In doing so, it demonstrates that CE occurs by virtue of, and is typified by, sensemaking processes that reproduce and shape a customer's habituated value lens, which perceives, assesses, and determines VCC and thus provides a basis for further customer engagement.